Converts to the real Catholicism and the making of continental philosophy - Baring, Edward, 1980- (Harvard University Press, 2019)
In the middle decades of the twentieth century phenomenology grew from a local philosophy in a few German towns into a movement that spanned Europe. In Converts to the Real, Edward Baring uncovers an unexpected force behind this prodigious growth: Catholicism. Participating in a tightly-knit transnational community, Catholics helped shuttle ideas between national traditions that were otherwise inward-looking and parochial. In the first half of the twentieth century, they wrote many of the first articles and books introducing phenomenological ideas to new contexts. They even organized the rescue of Edmund Husserl's manuscripts out of Nazi Germany in 1938. But the Catholic fascination with phenomenology was intermixed with a profound anxiety. Catholics worried that phenomenological ideas might prove dangerous to the faith, a possibility exemplified by the intellectual trajectory of Martin Heidegger, whose movement away from the Church was facilitated by his reading of Husserl. Converts to the Real uncovers a surprising genealogy for post-war European thought, with important implications for our understanding of the process of secularization and for the set of schools and ideas we now call "continental philosophy."--